Investigation of the role of sulfide oxidation in the gill-associated microbiota of freshwater mussel Limnoperna fortunei - Peng, Yu; Huang, Duanyi; Li, Juechun; Sun, Xiaoxu; Zhang, Qifan; Zhang, Ruijian; Yang, Rui; Li, Baoqin; Kong, Tianle; Xiong, Zhiming; Huang, Ying; Chang, Zhibing; et al. (Frontiers in Microbiology, 2025)
IntroductionLimnoperna fortunei is a notable invasive freshwater species, altering structure and function of natural and engineered aquatic ecosystems. The host-associated microbiomes play a critical role in the survival and thriving of L. fortunei, with the gill-associated microbiomes being particularly significant due to their involvement in filter feeding, nutrient metabolism, and symbiosis. However, research on microbiomes associated with L. fortunei remains limited, and studies specifically focusing on gill-associated microbiota are scarce, leaving a significant gap in our understanding of their ecological roles.MethodsIn this study, gill-associated bacterial communities of the L. fortunei were compared with their surrounding water microbial populations in the largest water diversion projects (the Middle Route of the South-to-North Water Diversion Project) to elucidate their environmental adaptations and potential contribution to their hosts. Analyses included assessing bacterial diversity and composition, conducting Neutral Community Model (NCM) analysis to explore community assembly processes, constructing an environmental-microbial co-occurrence network to identify key environmental factors, and performing metagenomic analysis of gill samples to investigate functional genes.ResultsSignificant variations were observed in bacterial diversity and composition between gills and surrounding water. Sulfur oxidizing bacteria Pirellula, SM1A02, and Roseomonas were significantly enriched in gill-associated microbiota. Neutral community model (NCM) analysis unveiled that the assembly of gill microbial communities was primarily governed by stochastic processes, constrained by determined processes. Moreover, environmental-microbial co-occurrence network identified reduced sulfur as the key factor shaping the composition of bacterial communities. Metagenomic binning of gill samples further revealed that metagenome assembled genomes associated with Pirellula within the phylum Planctomycetota contained functional genes related to sulfide oxidation and resistant to oxidative stress.DiscussionThis study provides systematic insights into the microbial community diversity, assembly patterns, and functional characteristics of L. fortunei gill-asscociated microbiota, contributing to a mechanistic understanding of their ecological roles.